DETERMINAN PENGUNGKAPAN INFORMASI ATRIBUSI DAN DAMPAKNYA TERHADAP PERSISTENSI LABA - Suripto, Bambang (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
Previous studies indicated that there were two common types’ performance explanations disclosures by Indonesian company’s managers in annual report: (1) performance attribution and (2) accounting explanation (Suripto 2013). Performance attribution disclosures were more useful and expensive than accounting explanation (Aerts et al. 2013). This study is conducted to obtain empirical answers for two research questions: (1) whether firm characteristics affect performance attribution disclosure extent in the annual report and (2) whether performance attribution information is useful to evaluate company earnings persistency. Content analysis was conducted on 594 annual reports to obtain data performance attribution disclosures. The empirical test results showed that firm’s size and corporate governance have a positive effect on performances attribution disclosures. In addition, the research results showed that performance attribution disclosures were useful for evaluating revenue persistence.